Inhibiting effects by Fe2O3 on combustion and explosion characteristics of ABS resin. (May 2021) - Feng, Chih-Tsung; Lin, Wei-Cheng; Luo, Jing-Wen; Shu, Chi-Min
Abstract: The global increase in the use of, and reliance on, plastics has prompted the demand for acrylonitrile-butadiene-styrene (ABS) resin in various fields. With this increased requirement, numerous failures have occurred in the ABS process. Those incidents, resulting from electrostatic discharge, powder accumulation, heat accumulation, construction sparks, and plant fires, have caused dust fire and explosions. In this study, the ABS resin was gleaned from the site and tested for its explosion parameters, including minimum ignition temperature of dust cloud ( MIT C ), minimum ignition energy ( MIE ), and minimum explosion concentration ( MEC ). To improve loss prevention in the manufacturing process, ferric oxide (Fe2 O3 ) as an inert additive was added in the ABS powder. According to the MIE test, Fe2 O3 has an apparent inhibiting effect on dust explosion for the ABS dust. With the proportion of Fe2 O3 increased from 25 to 50 mass% in ABS, the MIE increased from 67 to 540 mJ. The explosion tests via 20-L apparatus indicated that Fe2 O3 mixed with ABS could not increase the MEC significantly. However, the explosion pressure dropped by increasing in the ratio of Fe2 O3 in ABS. This inerting strategy of ABS was deemed to substantially lessen the probability and severity of fire and explosion. Highlights: Samples with larger particle size distribution (σD) performed the weak explosibility than the smaller. Increasing reaction onset temperature ( T 0 ) showed the high-temperature resistance was enhanced by adding sand and Fe2 O3 . Due to the non-flammability of Fe2 O3, the MIT C of samples A–C did not attenuate despite decreasing MIT C and particle size.